Investigation into the effects of temperature levels and relative humidity effects on Nigella (Nigella sativa L.) seed storage - Zeinab Savaedy; Abdolmahdi Bakhshandeh; seyed ata Siadat; Amin Lotfi Jalal Abadi; Seyed Amir Moosavi (علوم و فناوری بذر ایران)
In order to study the effects of storage temperature and humidity on seed germination properties and seedling growth of (Nigella sativa L.), a factorial experiment was conducted at the seed technology laboratory of Agricultural Sciences and Natural Resources University of Khuzestan based on the randomized block design with four replications.    Experimental treatments were different levels of relative humidity during storage (33, 75 and 100%), storage temperatures (30, 35, 40 and 45 oC) and storage durations (24, 48, 72 and 96 hour) and control. Results showed that increase of storage temperature and relative humidity led to lower seed germination percentage and germination rate, reduction in the root and shoot length and seedling vigor indices, while mean germination time and electrical conductivity increased. Among experimental treatments, the severe deterioration was observed at 100% relative humidity and 45 oC with the durations of 96 hour and at the medium deterioration treatments, of Nigella seeds were resealed from primary dormancy and seed germination was increased, accordingly. Fitted linear regression models by experimental treatments vs germination indices and seedling growth showed that except mean germination time of seed germination, all the traits exhibited linear relationship with three independent variables studied in this experiment